Thermal Comfort Level Based on the Temperature Humidity Index Value in Bandung City - Nasihien, Alfiansyah Dhiya’ulhaq; Hasyim, Abdul Wahid; Usman, Fadly (LPPM of NAROTAMA UNIVERSITY, 2024)
The city of Bandung is one part of the Greater Bandung Area which has been designated as a National Activity Center (PKN) which has a role as a collection and distribution center on international, national, and several provincial scales. This has resulted in a high level of development driven by the pace of the economy and population growth which continues to increase in the city of Bandung, resulting in an increase in the need for built-up land which is accompanied by a decrease in non-built land, especially green open space, so that it can affect the temperature and humidity of the air as well as the thermal comfort of the microclimate or temperature. This research aims to identify the distribution of THI as a measure of the level of thermal comfort in Bandung City. The approach is remote sensing, specifically utilizing Landsat 8 OLI/TIRS image processing for 2013 and 2023 on Google Earth Engine Software. The data processing process goes through several stages, including NDVI processing, land cover classification, surface temperature, and THI. After going through these stages, it was found that the distribution of temperature humidity index values in 2023 in Bandung City was dominated by the uncomfortable class (>26°C).